Profitabilitas Dalam Kemampuannya Memoderasi Faktor – Faktor Yang Mempengaruhi Nilai Perusahaan - Anita Tarihoran; Suriani Ginting (Fakultas Bisnis Universitas Mikroskil, 2023)
The research aims to test and analyze the ability of profitability to moderate the factors that affect the value of the company. Issuers used as research objects are non-financial companies listed on the Indonesia Stock Exchange in 2019 – 2020. The population in this study totaled 675 companies and using the purposive sampling method obtained a sample of 129 companies. The data analysis method used was Partial Least Square using a two-stage approach model using the SmartPLS 3 statistical software tool. The results show that the variable leverage, liquidity, dividend policy, and tax aggressiveness have no effect on firm value in non-financial companies listed on the Indonesia Stock Exchange for the 2019- 2020. Meanwhile, profitability has not been able to moderate the relationship between firm value and the factors that influence it.